Останні тенденції та чинники впливу на розвиток сільських територій в контексті євроінтеграційних процесів - Шебештень Едіна; Sebestyén Edina; Edina Shebestyen; Любка Віталій; Vitalii Liubka (Видавничий дім «Гельветика», 2022)
Резюме. Робота розкриває останні тенденції та чинники впливу на розвиток сільських територій. Серед чинників, які впливають на розвиток сільських територій виділено: соціальні, інформаційно-цифрові, інституційних перетворень, туристично-рекреаційні, інвестиційні, територіальні (регіональні), виробничі та економічні. Здійснено коротку їх характеристику. Запропоновано платформу диференціації розвитку сільських територій, з врахуванням сукупності чинників, які впливають на їх розвиток; функції, які вони виконують в сучасному ринкову суспільстві та з врахуванням останніх тенденції розвитку території. Авторами сформовані останні тенденції розвитку сільських територій, серед яких: забезпечення сталого розвитку аграрного комплексу України; мотивація розвитку сільського господарства; ефективна та прозора система державної підтримки; реалізація програм соціального партнерства; децентралізація.

Abstract. The work reveals the latest trends and factors influencing the development of rural areas. Among the factors that influence the development of the rural regions, the following are highlighted: social, informational, and digital, institutional transformations, tourist and recreational, investment, territorial (regional), industrial and economic. A brief description of them has been made. A platform for differentiation of the development of rural areas is proposed, taking into account the set of factors that affect their development, the functions they perform in the modern market society, and taking into account the latest trends in the development of the territory. The authors formed the latest trends in developing rural areas, including ensuring the sustainable development of Ukraine’s agrarian complex, motivating agricultural development, effective and transparent system of state support, implementing social partnership programs, and decentralization. It was established that the development of rural areas is a component of the agricultural policy of Ukraine. The article also focuses on the fact that the development of rural areas should be aimed at waste-free production of farm products, organic, safe output, and compliance with the requirements of the concept of sustainable development. This, in turn, will reduce the level of harmful emissions into the environment, improve the level of ecology and preserve and improve the general state of natural resources. The purpose of this article is to study the essence and significance of factors that affect the development of rural areas. To analyze the influence of elements on the development of the rural regions, general scientific and special research methods were applied. In particular, inductive and deductive methods were used to substantiate the structural components of the differentiation platform for the development of rural areas. The way of comparison was applied when investigating the functions of rural areas. The graphic method was used to visualize the differentiation platform of the development of the rural regions. The abstract-logical method is used for theoretical generalizations and the formation of conclusions.
Latest trends and factors of influence on the development of rural areas in the conditions of european integration processes
Редакційна колегія: http://www.visnyk-econom.uzhnu.uz.ua/index.php/redkolegiya
Зміст: http://www.visnyk-econom.uzhnu.uz.ua/index.php/44-2022
Keywords: розвиток сільських територій; сільське господарство; чинники; тенденції розвитку; територія; rural development; agriculture; factors; trends of development; rural